Relationship Between C-Reactive Protein Levels and Leucocytes Counts in Typhoid Fever Pediatric Patients - Saktiningsih, Hari; Nurdiana (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Typhoid fever was an infectious disease caused by Salmonella enterica serovar Typhi and Enteritidis. Laboratory tests most commonly performed in cases of typhoid fever included leukocyte count and C-reactive protein (CRP) measurement. Leukocytes played a role in the immune response to infection, while CRP increased as a result of the inflammatory response and was therefore used as an indicator of disease activity. This research intended to examine the correlation amongst C-reactive protein (CRP) levels and leukocyte count in pediatric patients with typhoid fever. This was an observational analytic descriptive study with a cross-sectional design. The study sample consisted of CRP levels and leukocyte count results obtained from the medical records of 84 pediatric patients aged 6 to 17 years diagnosed with typhoid fever at RSIA Brawijaya Duren Tiga during the period of July to December 2025, selected utilizing a purposive sampling technique. The findings of univariate and bivariate analyses showed that most pediatric typhoid patients were female, totalling 48 (57%) children, and the longest duration of fever was 7 days, observed in 53 (63%) children. The most common CRP finding was abnormal levels in 46 (55%) children, with the highest level reaching 168.80 mg/L. The leukocyte count was most commonly within the normal range in 44 (52%) children. Correlation test results indicated a significant correlation amongst CRP levels and leukocyte count, with a moderately strong positive correlation, as evidenced by a significance value of 0.002 and a correlation coefficient of r = 0.326.